Strangulated intestinal hernia through a drain site - Falidas, Evangelos (2011)
INTRODUCTION: Intra-abdominal drains have been widely used in order to prevent intra-abdominal fluid accumulation and detection of anastomotic leakage. PRESENTATION OF CASE: We herein report a case of small bowel herniation followed by strangulation in an 82 year old woman who had undergone sigmoidectomy for colorectal cancer. DISCUSSION: Although several complications related to drain usage such as drainsite infection, hemorrhage and intestinal perforation may occur, intestinal incarceration through drain site is rarely reported. CONCLUSION: Drains must be used with caution and only if indicated. Careful insertion, regular post-operative or post-removal inspection is strongly recommended.